MicroRNA‐125a‐5p Is a Downstream Effector of Sorafenib in Its Antiproliferative Activity Toward Human Hepatocellular Carcinoma Cells. Issue 7 (16th February 2017) - Potenza, Nicoletta; Mosca, Nicola; Zappavigna, Silvia; Castiello, Filomena; Panella, Marta; Ferri, Carmela; Vanacore, Daniela; Giordano, Antonio; Stiuso, Paola; Caraglia, Michele; Russo, Aniello
Abstract : Sorafenib is an antitumor drug for treatment of advanced hepatocellular carcinoma (HCC). It acts as a multikinase inhibitor suppressing cell proliferation and angiogenesis. Human microRNA‐125a‐5p (miR‐125a) is endowed with similar activities and is frequently downregulated in HCC. Looking for a potential microRNA‐based mechanism of action of the drug, we found that sorafenib increases cellular expression of miR‐125a in cultured HuH‐7 and HepG2 HCC cells. Upregulation of the microRNA inhibited cell proliferation by suppression of sirtuin‐7, a NAD(+)‐dependent deacetylase, and p21/p27‐dependent cell cycle arrest in G1. Later, recruitment of miR‐125a in the antiproliferative activity of sorafenib was inquired by modulating its expression in combination with the drug treatment. This analysis showed that intracellular delivery of miR‐125a had no additive effect on the antiproliferative activity of sorafenib, whereas a miR‐125a inhibitor could counteract it. Finally, evaluation of other oncogenic targets of miR‐125a revealed its ability to interfere with the expression of matrix metalloproteinase‐11, Zbtb7a proto‐oncogene, and c‐Raf, possibly contributing to the antiproliferative activity of the drug. J. Cell. Physiol. 232: 1907–1913, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Upregulation of the microRNA inhibited cell proliferation by suppression of sirtuin‐7, a NAD(+)‐dependent deacetylase, and p21/p27‐dependent cell cycle arrest in G1. Intracellular delivery of miR‐125a had no additive effect on the antiproliferative activity of sorafenib, whereas a miR‐125a inhibitor could counteract it. miR‐125a interfered with the expression of matrix metalloproteinase‐11, Zbtb7a proto‐oncogene, and c‐Raf, possibly contributing to the antiproliferative activity of the drug.